2010
DOI: 10.1007/s00128-010-0178-7
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Pesticide Residues in Rice Grain by Solvent Extraction, Column Cleanup, and Gas Chromatography-Electron Capture Detection

Abstract: A simple, easy, cheap and efficient analytical method for determination of multiple pesticide residues including organochlorine, organophosphorus, synthetic pyrethroids and herbicides in rice grain by capillary gas chromatography is developed. The quantification of residues was done by capillary gas chromatography with a μ-ECD detector and a HP-5MS capillary column. Known amounts of a mixture of pesticides were added to grain prior to extraction, cleanup and GC-determination. Recoveries were checked at two for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…In the present study, extraction and cleanup steps were performed according to Uddin et al 2011, with some modifications in the cleanup step. Dry mixture of acidic alumina and activated charcoal was introduced into glass column with the help of aluminum foil instead of slurry of that mixture in dichloromethane to reduce the amount of DCM used in the cleanup step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, extraction and cleanup steps were performed according to Uddin et al 2011, with some modifications in the cleanup step. Dry mixture of acidic alumina and activated charcoal was introduced into glass column with the help of aluminum foil instead of slurry of that mixture in dichloromethane to reduce the amount of DCM used in the cleanup step.…”
Section: Resultsmentioning
confidence: 99%
“…The spiked samples were kept for 24 h before extraction, for allowing time for insecticide penetration into the samples. The extraction and cleanup were undertaken as method described by Uddin et al (2011). For this, 4 g of ground wheat was placed in 50 mL centrifuging tube and shaken vigorously after addition of 40 mL mixture of acetone:methanol (1:1).…”
Section: Methodsmentioning
confidence: 99%
“…To minimize the problem, protective insecticides are misused, which arises concern about the quality of the products that reach consumers' table (Prestes et al 2009). Consumers have increasingly demanded foods without pesticides residue (Dórea and Sobrinho 2004;Uddin et al 2011 oxidation, photochemical degradation and chemical oxidation have been studied to optimize pesticide residue degradation (Chiron et al 2000;Selma et al 2008). Recent studies have shown ozone gas efficiency in the removal of pesticide residues (Wu et al 2007) and mycotoxins in plant products (Inan et al 2007;Alencar et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recoveries of 80-120% were attained for most analytes, and the LOQs ranged from 10-50 ng/g. Solvent extraction to analyze for multiple pesticide residues in rice grains was reported by Uddin et al (2011). The recoveries were checked at 0.1 and 0.5 µg/g, and the average recoveries were 74%-111%.…”
Section: Water Environment Research Volume 84 Number 10-copyright ©mentioning
confidence: 99%